TAS-102 Monotherapy and Combination Therapy with Bevacizumab for Metastatic Colorectal Cancer - Cheng-Jiang Liu; Ting Hu; Ping Shao; Wu-Yang Chu; Yu Cao; Feng Zhang (Gastroenterology Research and Practice)
Objective. To evaluate the effectiveness and safety of TAS-102 monotherapy and combination therapy with bevacizumab in the treatment of metastatic colorectal cancer. Methods. The PubMed, Web of Science, MEDLINE, and Cochrane Library databases were searched for the literature on TAS-102 treatment of metastatic colorectal cancer. Extracted data include median overall survival (mOS), median progression-free survival (mPFS), and the incidence of adverse events for meta-analysis. Results. Our study found that the mOS of patients treated with TAS-102 monotherapy was 6.95 (95% CI: 6.26-7.72) months and the mPFS was 2.53 (95% CI: 2.31-2.78) months. The mOS in patients treated by TAS-102 combined with bevacizumab was 10.41 (95% CI: 8.40-12.89) months, and the mPFS is 4.35 (95% CI: 3.05-6.20) months. In the control experiment, the patients’ mOS and mPFS were improved. TAS-102+B vs. TAS-102 (OR=0.41, 95% CI: 0.18-0.93; OR=0.72, 95% CI: 0.63-0.83) and TAS-102 vs. placebo (OR=0.44, 95% CI: 0.29-0.67; OR=0.51, 95% CI: 0.42-0.62) were studied to actively prevent the occurrence of neutropenia, leukopenia, febrile neutropenia, anemia, and vomiting. Conclusion. TAS-102 monotherapy and combination therapy with bevacizumab can significantly improve the survival of patients and prevent specific adverse events from happening.